Wardah Marketing Communication Strategy to Improve Brand Image During Covid-19 Pandemic - Kathleen, Sabrina; Nurmelinda, Risma Dewi; Koeswandi, Tika Annisa Lestari; Budiman, Arief; Yusuf, Ismail (A Social Science and Entrepreneurship Journal, 2021)
This study aims to determine the effect of the marketing communication strategy that has been carried out by Wardah on his consumers in the midst of the Covid-19 pandemic. Using a qualitative descriptive method with an exploratory descriptive approach. Techniques for data analysis use interactive qualitative descriptive methods in the first form, namely collecting data then data reduction, data display, and conclusions/ interpretive verification. Based on the results of the study, it was concluded that Wardah had used the right communication strategy during this pandemic to be able to maintain their brand image. Consumers remain loyal to Wardah because the brand image is very well formed. The advice that can be conveyed to Wardah is to create something that attracts the attention of consumers while maintaining a good brand image in the midst of the current pandemic.